Podcast-Based of Audio Media for Bassketball Education - Siti Ukhdatul Laily; Febrita Paulina Heynoek; Rama Kurniawan (Universitas PGRI Palembang, 2023)
Condition of basketball lectures during the covid-19 pandemic which was carried out in a hybrid manner, resulting in less than optimal learning activities. In addition, based on each individual's different learning styles such as audio, visual and kinesthetic, it is important to have new learning media to help increase the effectiveness and attractiveness of learning activities. The purpose of this research is to develop a new learning media based on audio podcasts that can be accessed through the spotify platform. The method used is a research model from Lee & Owen's ADDIE theory (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique used a questionnaire filled out by research subjects, namely PJKR FIK UM students. This study went through several validation stages with details of 1 basketball material expert who produced an average of 92.48%, 1 learning expert with an average of 97.20 % and 1 media expert with an average of 92.80%. So that the product is declared feasible and valid for group testing. In the small group trial phase with 10 respondents consisting of 6 women and 4 men, the average calculation was 85.72%. Meanwhile, in a large group trial with 30 respondents, each 16 women and 14 men, the average calculation was 94%. It can be concluded that the development of podcast-based audio learning media is valid and feasible to use in learning.